D3S - a distributed storage service - Lopes, Rui Pedro (2014)
The Internet growth allowed an explosion of service provision in the cloud. The cloud paradigm dictates the users` information migration from the desktop into the network allowng access averyhere, anytime. This paradigm provided a adequate environment to the emergency of online storage services, such as Amazon S3. This kind of services allows storing digital data in a transparent way, in a pay-as-you-go model. This paper describes an implementation of an S3 compatible cloud storage service based on peer-to-peer networks, in particular, through the BitTorrent protocol. This approach allows taking advantage of the intrisic features of this kind of networks, in particular possibility for simultaneous downlouading of pieces from different locations and the fault tolerance.